Aspirin alleviates cardiac fibrosis in mice by inhibiting autophagy - LIU Ping-ping; LIU Hong-hong; SUN Shu-hong; SHI Xing-xing; YANG Wan-cheng; SU Guo-hai; ZHAO Jing (Acta Pharmacologica Sinica; Vol 38, No 4 (April 2017): Acta Pharmacologica Sinica, 2017)
Aspirin (ASA) is a cardioprotective drug with anti-cardiac fibrosis action in vivo. This study was aimed to clarify the anti-cardiac fibrosis action of ASA and the underlying mechanisms. Two heart injury models (injection of isoproterenol and ligation of the left anterior descending branch) were used in mice to induce cardiac fibrosis. The animals were treated with ASA (10 mg·kg-1·d-1, ig) for 21 and 14 d, respectively. ASA administration significantly improved cardiac function, and ameliorated heart damage and fibrosis in the mice. The mechanisms underlying ASA’s anti-fibrotic effect were further analyzed in neonatal cardiac fibroblasts (CFs) exposed to hypoxia in vitro. ASA (0.5–5 mmol/L) dose-dependently inhibited the proliferation and Akt phosphorylation in the CFs. In addition, ASA significantly inhibited CF apoptosis, and decreased the levels of apoptosis markers (cleaved caspase 3 and Parp1), which might serve as a side effect of anti-fibrotic effect of ASA. Furthermore, ASA dose-dependently inhibited the autophagy in the CFs, as evidenced by the reduced levels of autophagy marker LC3-II. The autophagy inhibitor Pepstatin A (PepA) promoted the inhibitory effect of ASA on CF proliferation, whereas the autophagy inducer rapamycin rescued ASA-caused inhibition of CF proliferation, suggesting an autophagydependent anti-proliferative effect of ASA. Both p38 inhibitor SB203580 and ROS scavenger N-acetyl-cysteine (NAC) significantly decreased Akt phosphorylation in CFs in the basal and hypoxic situations, but they both significantly increased LC3-II levels in the CFs. Our results suggest that an autophagy- and p38/ROS-dependent pathway mediates the anti-cardiac fibrosis effect of ASA in CFs. As PepA and SB203580 did not affect ASA-caused inhibition of CF apoptosis, the drug combination will enhance ASA’s therapeutic effects.